Navigating the New Retail Landscape: How Omnichannel Integration and Deal Proneness Influence Fashion Showrooming in Indonesia - Febriskamadya, Muhammad Husein; Constantia, Eirene Kenny; Arious, Edfent; Simanjuntak, Evi Rinawati (International Review of Management and Marketing, 2026)
Showrooming has become one of the most challenging phenomena in omnichannel retailing, particularly within the fashion category where consumers tend to try products in physical stores but complete their purchases online. This research explores how omnichannel integration can affect showrooming intention through cognitive and affective customer experience, while also examining the moderating role of deal proneness among Indonesian fashion consumers. This research employs the Stimulus-Organism-Response (S-O-R) framework and analyzes 421 data from consumers who visited both physical and online retail channels using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research reveals that Integrated Information Access is the strongest driver of cognitive experience, whereas Integrated Customer Service and Integrated Order Fulfillment had the greatest influence on affective experience. More importantly, Affective Customer Experience showed a stronger influence on Showrooming Intention than cognitive experience. This suggests that showrooming is driven not only by rational evaluation but also by emotional engagement during the shopping journey. In addition, high deal-prone shoppers were more likely to engage in showrooming. These findings offer critical perspectives for fashion retailers to retain consumers in a competitive digital retail environment.